A revised stratigraphical framework for the Quaternary deposits of the German North Sea sector: a geological‐geotechnical approach. (10th May 2017) - Coughlan, Mark; Fleischer, Matthias; Wheeler, Andrew J.; Hepp, Daniel A.; Hebbeln, Dierk; Mörz, Tobias
Abstract : Using extensive data sets from three separate areas in the German North Sea sector, consisting of seismic grids, cores and in‐situ cone penetration tests (CPT), we have established a revised stratigraphical framework for the mid to late Quaternary deposits of the German North Sea sector. This framework consists of four regional unconformities and 15 other local unconformities derived from seismic profiles. Using these unconformities, along with lithological and geotechnical data, it was possible to define and correlate 14 major units and 21 subunits within the framework. The Quaternary cover in the area is characterized by a variety of environmental settings ranging from glacial terrestrial and fluvial to lacustrine as well as brackish and marine environments with associated erosion, reworking and deposition. The complexity of Quaternary deposits within the area is explained by its history of repeated ice advances interrupted by marine transgressions and exposed periglacial landscapes. Within the framework, eight buried tunnel valleys and two shallow buried river valleys are identified from seismic profiles with four phases of tunnel valley generation inferred. These phases of tunnel valley generation are associated with the Elsterian (three) and Saalian (one) glacial stages. Infill of these tunnel valleys consists of glaciofluvial sands, thick sequences of marine and lacustrine fine‐grained sediments and some reworked till remnants. Elsewhere, extensive tabular units have formed consisting of marine and fluvial sediments. We compare this new stratigraphy with previous stratigraphies for the German North Sea sector, attribute informal stratigraphical names and offer preliminary correlations with established stratigraphies from other sectors of the North Sea.